Sistem Pengembangan dan Pemberdayaan Budaya Organisasi Madrasah/Sekolah - Makmur Syukri; Fachruddin Azmi; Mhd Joni Marpaung; Faisal Fahmi Rambe; M. Yasir Ridho (Departement of Mathematics Education, 2024)
This study aims to examine the development system and empowerment of organizational culture in Aliyah Al-Washliyah 49 Pasar Lembu Islamic High School. A strong and positive organizational culture plays a crucial role in improving the quality of education and creating an optimal learning environment. The research methodology used in this study is qualitative, involving surveys and case studies in Aliyah Al-Washliyah 49 Pasar Lembu Islamic High School, which represents various levels of education and different characteristics of organizational culture. Data were collected through interviews, observations, and analysis of relevant documents. The findings of this study indicate that the development system and empowerment of organizational culture in the madrasah/school play an important role in building an inclusive, collaborative, and learning-oriented culture.